ANALYZING THE EFFECT OF PRODUCTION RISK AND TIME PREFERENCE ON THE USE AND CHOICE OF IMPROVED LIVESTOCK FEEDING PRACTICE IN ETHIOPIA - Muuz Hadush (Agricultural Socio-Economics Journal, 2019)
A number of improved feeding practices such as stall feeding, rotational grazing, and tethering can help increase livestock productivity in Ethiopia. The main aim of this paper is to determine what factors affect the adoption of on such improved feeding practice; i.e.  Stall Feeding (SF) and the choice of animal or season for its application. A bivariate probit model was estimated using observations from 367 rural farmers in Northern Ethiopia.Production risk and the frequency of shock are found to be key determinants. As expected, the results from bivariate model revealed that the expected yield positively influenced SF adoption decision and its full-year application while yield variability and risk of yield failure had a negative effect on SF adoption decision and its full-year application. Likewise, previous animal shocks positively contribute to SF adoption.  The major contribution of this paper is its explicit treatment of production risk, shock and time preference in the decision to adopt and apply SF. Expected benefits that the farmer can derive from low production risk due to SF adoption should be included in the promotion agenda of SF practice. The implication is that intervention that reduces the variance of return and exposure to downside risk are some desirable in the adoption and choice decision.